Reframing Kiruna’s Relocation—Spatial Production or a Sustainable Transformation? - Aslı Tepecik Diş; Elahe Karimnia (Sustainability, 2021)
Due to the expansion of nearby mining operations, the city of Kiruna, an arctic city in Sweden, has been undergoing a massive urban transformation, led by the mining company, Luossavaara-Kiirunavaara Aktiebolag (LKAB), which is the largest iron ore producer in the EU. This paper explores this relocation in a three-sphere transformation framework that has sustainability as the outcome (practical sphere), and analyses it as a socio-spatial transformation process, including political decisions as its driving forces (political sphere), to examine how this outcome and decisions represent individual and collective values (personal sphere). The analysis of three spheres is used as a tool to understand how and why Kiruna’s urban transformation is deemed to be sustainable, as it claims, and which it is being globally acknowledged for. Methods include analysis of Kiruna’s new master plan, media representations, and interviews with key actors of the project, who include municipal planners; the mining company’s planning developers; consultants, as the designers of ‘Kiruna 4-ever’ and the new city center; as well as the city’s residents. The analysis is a critique of the approaches that fit this project into either the critique of market-led spatial production, or as an example of best practice, based on its participatory processes. Results indicate that although Kiruna’s relocation is claimed to be a transformation of collective values, practical and technical transformations were dominant, which represents only partial responses in the framework. Therefore, a multi-voice narrative challenges the sustainability of Kiruna’s transformation.